2011
DOI: 10.1253/circj.cj-11-0118
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Myocardial Redox State and Matrix Metalloproteinase Activity in Patients on Left Ventricular Assist Device Support

Abstract: Background: Redox aminothiols have been reported to modulate the activity of recombinant metalloproteinases (MMP). The aim of the present study was to investigate the effects of myocardial redox state on the activities of MMP-2 and -9 implicated in cardiac remodeling in end-stage heart failure patients supported by left ventricular assist device (LVAD). Methods and Results:During heart transplant (HT) surgery, myocardial specimens (MS) from right ventricular walls and LV walls were obtained from 7 LVAD recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…Even though signs of reverse remodelling are present in the contractile proteins, the LVAD does not appear to improve oxidative stress levels in the myocardium. This result is similar to that seen by Caruso et al [29], showing that LVAD recipients had increases in the myocardial redox state compared to heart failure patients without LVAD support.…”
Section: Oxidative Stresssupporting
confidence: 91%
“…Even though signs of reverse remodelling are present in the contractile proteins, the LVAD does not appear to improve oxidative stress levels in the myocardium. This result is similar to that seen by Caruso et al [29], showing that LVAD recipients had increases in the myocardial redox state compared to heart failure patients without LVAD support.…”
Section: Oxidative Stresssupporting
confidence: 91%
“…Previous studies have shown increased cardiac expression of profibrogenic genes including TGFβ1 in patients with end-stage heart failure referred for LVAD support 23, 24 . In both studies, higher levels of TGFβ1 were observed in subjects requiring LVAD support until cardiac transplantation, suggesting that TGFβ1 may limit myocardial recovery by promoting tissue fibrosis.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, data demonstrating that myocardial TGF-β1 levels are elevated in LVAD patients suggest that the hemodynamic benefits of LVAD insertion may not reverse the increase in myocardial TGF-β1 associated with HF. 39…”
Section: Discussionmentioning
confidence: 99%